Effect of physical exercise intervention on mood and frontal alpha asymmetry in internet gaming disorder. (March 2020) - Hong, Ji Sun; Kim, Sun Mi; Kang, Kyoung Doo; Han, Doug Hyun; Kim, Jeong Soo; Hwang, Hyunchan; Min, Kyoung Joon; Choi, Tae Young; Lee, Young Sik
Abstract: Purpose: We aimed to evaluate the effect and neurophysiological mechanism of physical exercise intervention combined with cognitive behavioral therapy on mood and frontal alpha asymmetry in the treatment of Internet gaming disorder. Methods: Fifty male adolescents with Internet gaming disorder were randomly assigned to one of two groups. In the cognitive behavioral therapy + physical exercise group (CBT + PE group, n = 25), participants underwent eight sessions of cognitive behavioral therapy and six sessions of exercise intervention; in the cognitive behavioral therapy-only group (CBT-only group, n = 25), participants underwent eight sessions of cognitive behavioral therapy and six sessions of supportive counseling. A resting quantitative electroencephalogram, Young Internet Addiction Scale, the Korean Attention Deficit Hyperactivity Disorder Rating Scale, Beck Depression Inventory, and Beck Anxiety Inventory were evaluated before and after the intervention. Results: Although both the CBT + PE and CBT-only groups showed a significant reduction in Beck Depression Inventory and Young Internet Addiction Scale scores, indexing a decrease in depression, this effect was more pronounced in the CBT + PE group than in the CBT-only group. An increase in the F4–F3 and F8–F7 frontal alpha asymmetry values was more pronounced in the CBT + PE group than in the CBT-only group. Conclusion: Physical exercise intervention in combination with cognitive behavioral therapy for individuals with Internet gaming disorder seems to improve the severity of internet use and depressive mood and enhance left prefrontal activation. Graphical abstract: Image 1 Highlights: Physical exercise for Internet gaming disorder improved the severity of internet gaming usage. Physical exercise for Internet gaming disorder improved the level of depressive mood. Physical exercise intervention enhanced the relative left prefrontal activation. The relative left prefrontal activation may be relevant with motivational approach.